The relationship between infectious disease history and child development at the Sei Mencirim Community Health Center, Sunggal District Deli Serdang Regency 2022 - Situmorang, Khairunnisa; Munthe, Juliana; Simanjuntak, Katarina P.; Malau, Gomgom Marlina; Nafsiah, Siti; Lismayanti, Lismayanti (Science Midwifery, 2023)
Human development in Indonesia continues to progress, as stated by the Central Statistics Agency (BPS). An increase of 0.53 points to grow by 0.74 percent compared to 2018, where Indonesia's Human Development Index (HDI) reached 71.92. The ability to suppress the incidence of infectious diseases such as Upper Respiratory Tract Infections (URTIs), Pneumonia, Pulmonary Tuberculosis, Hepatitis, Diarrhea and Malaria is one of the indicators of increasing HDI in Indonesia and is a success. Analyzing the Relationship between Infectious Disease History and Child Development in the Sei Mencirim Health Center Work Area, Sunggal District, Deli Serdang Regency in 2022. Observational/survey research, namely data collected from respondents using questionnaires or questionnaires without intervening in the research subjects. The type of research is descriptive analytical with cross-sectional. The research sample was part of mothers and toddlers at the Sei Mencirim Health Center, Sunggal District, Deli Serdang Regency in 2022 as many as 126 people. Using univariate and bivariate analysis. From the results of the statistical test, the majority of children with a history of diarrheal infectious diseases were 186 respondents (52.6%) and the minority of children with a history of ARI infectious diseases were 168 respondents (47.4%). The majority of children with appropriate development were 168 respondents (47.4%) and the minority of children with developmental deviations were 57 respondents (31%). And there is a relationship between a history of infectious diseases and child development at the Sei Mencirim Health Center, Sunggal District, Deli Serdang Regency in 2022 where the p-value is 0.017 (p <0.05).